X-ray study of dopant state in highly doped semiconductor single crystals - Shul’pina, I.L.; Kyutt, R.N.; Ratnikov, V.V.; Prokhorov, I.A.; Bezbakh, I.Zh.; Shcheglov, M.P. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2011)
Using Si(As, P, B) and GaSb(Si) study, possibilities of X-ray diffraction methods for diagnostics of highly doped semiconductor crystals in characterization of dopant state – whether it is in the crystals in the form of solid solution or under various stages of its decomposition – are shown. The combination of techniques of X-ray diffraction topography and high resolution X-ray diffractometry, higher sensitive to the crystal lattice strain than that traditionally used is taken as the basis for investigating the crystals with slight and strong absorption of X-rays. These methods were supplemented with digital processing of the topographic images of growth striations and electrical measurements.